Tungstate induced corrosion of some aluminium alloys in acidic chloride solution - An approach for controlling it with morpholine - Chaudhary R.S.; Yadav P.N.S.; Agarwal C.V. (My University, 2025)
The corrosion behaviour of some aluminium alloys (1060, 1100 and 3003) in acidic chloride solution (pH=1) have been studied in the presence of various concentrations of tungstate ions. The alloy most vulnerable to the effects of tungstate ions is 1100 followed by 1060 and 3003 alloys. After six hours of immersion the alloys exhibit 6 to 8 times higher corrosion rates compared to that in the blank solution containing only chloride ions. The experiments suggest that the tungstate ion stimulates the corrosion of aluminium by acting as a cathodic depolarizer. Morpholine effectively arrests the dissolution of the alloys in the blank electrolyte as well as in the presence of tungstate ions. Morpholine polarizes local cathodic sites to act as an inhibitor. Tungstate ions are not adsorbed on the surface in the presence of morpholine and a synergistic effect is obtained at higher concentrations of morpholine. A Langmuir adsorption isotherm has been used to explain the data. © 1983 Chapman and Hall Ltd.